Inuvialuit youth and environmental change research in Ulukhaktok - Pearce, T; Akhoaksion, J Jr; Bryant, C; Duerden, F; Ford, J D; Inuktalik, D; Inuktalik, K; Inuktalik, R; Irish, B; Joss, P; Kataoyak, F; Kataoyak, H; et al. (ArcticNet Inc., 2007)
Communities in the Canadian arctic have undergone rapid social, political, economic, and environmental changes in the past half century. These changes have often acted synergistically to affect Inuit livelihoods. In previous environmental change research in Ulukhaktok, adult community members and educators identified a concern for the sensitivity of youth to these changes, pointing to the continued loss of traditional land-based skills coupled with a lack of work-place relevant skills among the growing population of youth. This research worked with what are ultimately the second and third cohorts of settlement-reared community members who have limited experience with traditional subsistence beyond organized youth camps and occasional hunting trips, but comparatively more experience with southern media, formal education and training for wage labour employment. This research involved community youth as researchers to examine the vulnerability of youth in Ulukhaktok between the ages 8 and 24 years to changing conditions (e.g. who is vulnerable, to what conditions, how, and what is aiding or constraining the ability to adapt?) The research sample consisted of fifty-two youth with equal gender representation. To date, data has been collected through youth-led focus groups, participatory mapping, semi-structured interviews and analysis of secondary documents and reports. Current exposures identified by youth include, increased hazards when traveling on the sea ice and land in the spring (late May and June), concerns about proposed resource development, rising prices (e.g. fuel), substance abuse, and limited employment opportunities. Issues that contribute to the sensitivity of youth to these conditions and influence adaptation include, lack of confidence in local education standards, loss of traditional knowledge and skills, and lack of community activities and opportunities for youth. The next stages in the research are to further examine the interplay of these conditions using additional methods (e.g. pile sorting, free listing, follow-up interviews), and work with youth collaborators to identify policy entry points for enhancing the capacity of community youth to deal with future changes.